Manajemen Pengembangan Kebijakan Wisata Bahari Di Kawasan Ekonomi Khusus Mandalika Lombok Tengah: Studi Kasus Pantai Kuta - Alghisna Rahmatika; Tridoyo Kusumastanto; Agus Sadelie (Jurnal Manajemen, 2017)
This study aims to estimate the condition of economic value and demand ofthis particular area, estimate the carrying capacity as a condition of supply and formulatea strategy to determine the policy of marine tourism development with considerations ofsustainability of this Kuta Beach Area using a dynamic model. The method used forgathering the necessary data is purposive sampling, while the method of data analysis isthe analysis of supply with a carrying capacity analysis approach, analysis of tourismdemand with Travel Cost Method (TCM), financial feasibility analysis, prospectiveanalysis and dynamic analysis. The result of this research shows the number of tourists inKuta Beach is less than the carrying capacity of the island, so there isan opportunity toincrease the number of tourists. The result of demand analysis based on TCM is Rp8.614.874.595/year with an average of consumer surplus of Rp 42.250 with a number of203.899tourists in 2015. Based on the financial feasibility analysissuch as NPV, NetB/C, and IRR, it is concluded that the business of tourism in Kuta Beach is bothfinancially and economically feasible. The prospective analysis recommends a policybased on the opinion of the stakeholders that can be formulated as strategic implicationsand anticipatory actions in the Kuta Beach Area management plan. Dynamic analysisshows an increase in ecological, economic and social submodels.